The Influence of Mind Mapping Learning Strategies on Creativity and Sustainability Awareness of Elementary School Students in Motion Energy Learning - Hana Adawiyah; Wati Sukmawati (Postgraduate, University of Mataram, 2026)
This study aims to analyze the influence of Mind Mapping learning strategies on the creativity and sustainability awareness of elementary school students in motion energy learning. This study uses a quantitative approach with a quasi-experimental research method with a nonequivalent control group design. The research subjects consisted of elementary school students who were divided into experimental groups with the application of Mind Mapping strategies and control groups with conventional learning. The research data was collected through creativity test instruments, sustainability awareness questionnaires, and observation of learning activities, then analyzed using inferential statistical tests. The results of the study show that the application of the Mind Mapping strategy has a positive influence on increasing students' creativity and sustainability awareness in motion energy materials. Students who participate in Mind Mapping-based learning show better ability to organize concepts, develop ideas, and understand the relationship between energy use and environmental sustainability. These findings suggest that the Mind Mapping strategy can be an innovative learning alternative that supports the development of creative thinking skills and sustainability literacy in primary schools. Thus, the Mind Mapping strategy contributes to creating science learning that is more meaningful, contextual, and oriented towards 21st century competency development.